Analysis of Self-Awareness in Breaking Covid-19 Transmission - Erika Erika; Widia Lestari; Yulia Irvani Dewi; Kalpana Paudel (Indonesian Journal of Global Health Research, 2025)
COVID-19 infection transmits quickly and easily from one person to another. One way to prevent the transmission of COVID-19 is by increasing self-awareness. This study was to analyze self-awareness ability to breaking the COVID-19 transmission. This was a descriptive study with 518 respondents. Data were obtained through questionnaires with 40 statements using Goleman’s six indicators. The first indicator showed that 94.40% of respondents were able to recognize their feelings and could break COVID-19 transmission, the second indicator showed that 87.84% of respondents could recognize their strengths and weaknesses in preventing transmission, the third indicator showed that 88.42% possessed an independent attitude in deciding and preventing transmission, the fourth indicator showed that 86.88% of respondents could make informed decisions concerning the right ways to stop and prevent transmission, the fifth indicator stated that 87.26% were skilled in expressing their thoughts, feelings, opinions, and beliefs on transmission, and the last indicator showed that 88.22% of respondents could evaluate themselves concerning the virus transmission. Self-awareness could be raised through understanding. Nurses have responsibility in providing education to helping people be more aware of COVID-19 transmission by implementing health protocols: washing hands, wearing masks, maintaining distance, staying away from crowds, and reducing mobility.